PERSONAL EDUCATION TRAJECTORIES IN HIGHER EDUCATION INSTITUTIONS AND THEIR SIGNIFICANCE IN THE EDUCATIONAL PROCESS - Nishonov, Farkhod Musazhonovich (International Scientific and Current Research Conferences, 2024)
The article analyzes the need to introduce individual learning trajectories in higher education institutions and their role in the educational process. In the process of transition to person-oriented educational standards, the issues of individual characteristics of students and expansion of opportunities to choose the path of personal development are highlighted. The importance of socio-economic, individual-personal and motivational factors is studied in the process of creating individual educational trajectories. The article also discusses the importance of personalized learning trajectories in increasing students' motivation to study and facilitating personal development.